Salivary IgA concentration in diabetic patients compared to healthy controls - Farimah Sardari; Afshin Tahmasbi; Arash Ghanbarzadegan (Wolters Kluwer Medknow Publications, 2015)
Introduction: The alterations in salivary flow rate and its compositions could affect the development, symptoms, and severity of oral changes in diabetic patients. The aim of this study was to assess the concentration of salivary IgA in type I in comparison with type II diabetic patients and healthy controls. Materials and Methods: In this cross-sectional study, 25 patients with type I diabetes, 25 patients with type II diabetes, and 25 control subjects (12 subjects for the type I and 13 subjects for the type II) were enrolled. Unstimulated saliva samples were collected by spitting method and the concentration of salivary IgA was measured byenzyme-linked immunosorbent assay (ELISA) method. Results: The mean of salivary IgA in type I diabetic patients was 148.3 ± 38.7 μg/ml and in their controls was 65.8 ± 17.4 μg/ml (P < 0.001). In type II diabetic patients the mean of salivary IgA was 67.3 ± 20.6 μg/ml and in their controls was 63.3 ± 15.2 μg/ml. There was no significant difference between patients with type II diabetes and controls (P = 0.54). The mean of salivary IgA in patients with type I diabetes was significantly higher than in patients with type II diabetes (148.3 ± 38.7 versus 67.3 ± 20.6 μg/ml, respectively, P < 0.001). Conclusions: Level of salivary IgA in type II diabetic patients in comparison with their healthy control did not show any significant difference, but in type I diabetic patients was higher than that of healthy controls and type II diabetic patients.